A generalized theorem of mean values of an analytic function and an algorism of the determination of mean values - Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We prove the mean-value theorem for functions analytic in starlike domains, propose an algorithm for finding the functionof mean values, and study its analytic continuation. We present a differential equation for the function of mean values andthe interpretation of the Lagrange formula for analytic functions in terms of the theory of differential equations. The setof points of the initial values of the function of mean values is analyzed and the upper of the radius of expansion of thefunction of mean values in Taylor’s series is established.